OPTIMIZATION OF DIAGNOSTIC CRITERIA FOR LIVER AND PANCREAS DISEASES IN SMOKERS - Dilrabo J. Khalimova; Shukhrat Dj. Teshaev (Central Asian Journal of Medicine, 2025)
This study comprehensively explored the association between liver and pancreatic diseases and the consumption of tobacco products. A total of 45 patients diagnosed with liver diseases were included in the analysis, with detailed attention given to their tobacco use patterns and levels of nicotine dependence. Among these patients, 21 (46.7%) were identified as tobacco users. Similarly, an analysis of pancreatic diseases revealed that 23 (45.0%) patients with such conditions also reported using tobacco products. To quantify nicotine dependence, the Fagerström Nicotine Dependence Test (FNDT) was employed. The results indicated that 25 (26.0%) patients exhibited moderate nicotine dependence, while 10 (10.4%) were categorized as having high dependence. These data highlight the prevalence of tobacco use and its potential to exacerbate or contribute to the pathogenesis of hepatic and pancreatic disorders. The findings provide robust evidence of the significant role tobacco consumption plays in the development and progression of liver and pancreatic diseases. Tobacco is known to induce oxidative stress, promote inflammation, and impair cellular metabolism, mechanisms that are crucial in the pathophysiology of these organ systems. Additionally, tobacco-related compounds can directly damage hepatocytes and pancreatic cells, leading to fibrosis, steatosis, and an increased risk of malignancies such as hepatocellular carcinoma and pancreatic adenocarcinoma. This study underscores the importance of integrating tobacco cessation programs into the prevention and management strategies for liver and pancreatic diseases. Public health initiatives focused on reducing tobacco use could substantially decrease the burden of these conditions. Furthermore, the data highlight the need for tailored clinical interventions to address nicotine dependence among patients, particularly those with moderate and high levels of dependence, as part of a comprehensive therapeutic approach.